The Development and Evaluation of E-Learning for Professional Bus driver in Tanzania - Chacha, Marwa; Cuenen, Ariane; Nyaki, Prosper; Yasar, Ansar; Wets, Geert (EAI Endorsed Transactions on Smart Cities, 2025)
INTRODUCTION: Commercial buses serve as the predominant mode of public transportation in Tanzania, with 90% of travellers opting for them, especially for inter-regional and urban-rural journeys. Despite their widespread use, the affordability of this mode has led to a rise in road safety issues, resulting in an alarming surge in accidents, injuries, and fatalities. This paper explores the potential of eLearning as an alternative approach to enhance road safety in Tanzania's commercial bus sector.OBJECTIVES: The primary aim of this study is to assess bus drivers' perceptions of eLearning deployment and develop a tailored course to improve road safety practices. The overarching goal is to contribute to existing knowledge by creating a training course addressing identified gaps in the context of changing driver behaviours in Tanzania.METHODS: Employing a quantitative approach, data for this study were collected through an online survey on Qualtrics and semi-structured interviews over three weeks. Participants included individuals from the National Institute of Transport (NIT), Vocational Education Training Authority (VETA), road safety NGOs, and bus drivers in Dar es Salaam, in collaboration with the Land Transport Regulatory Authority (LATRA). The study involved the development of an eLearning package tailored for professional bus drivers, utilizing social network analysis techniques.RESULTS: The survey, comprising 153 participants, provided insights into bus drivers' preferences for a 35-hour theory and practical training program. Findings indicated a high willingness among drivers to adopt eLearning, with smartphones being the preferred device. The study also proposed a comprehensive eLearning package, incorporating six modules derived from research findings, to enhance road safety awareness among professional bus drivers.CONCLUSION: This research advocates for developing and implementing eLearning as a viable strategy to enhance road safety awareness and skills among commercial bus drivers in Tanzania. The proposed eLearning modules and the learning management system (LMS) aim to address the limitations of traditional in-person training, providing a flexible and accessible alternative. Future efforts should involve stakeholders, policy discussions, and integration with GPS tracking for targeted feedback and continuous improvement in driving behaviours. Overall, the introduction of eLearning has the potential to impact safety cultures within companies positively and contribute to reducing road traffic accidents.
Keywords: professional bus drivers; curriculum; e-Learning; Tanzania